Riksdag of the Estates: Bondeståndet - Språkbanken Text (University of Gothenburg, 2024)
Part of the data set "Riksdag of the Estates"

Del av Ståndsriksdagen
Ståndsriksdagen: Bondeståndet
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik